Week 144 Resistance Analysis of Elvitegravir/Cobicistat/Emtricitabine/Tenofovir DF Versus Atazanavir+Ritonavir+Emtricitabine/Tenofovir DF in Antiretroviral-Naïve Patients. Issue 5 (September 2014) - Kulkarni, Rima; Abram, Michael E.; McColl, Damian J.; Barnes, Tiffany; Fordyce, Marshall W.; Szwarcberg, Javier; Cheng, Andrew K.; Miller, Michael D.; White, Kirsten L.
Abstract : Objective: To describe baseline and emergent HIV-1 resistance to elvitegravir/ cobicistat/emtricitabine/tenofovir DF (EVG/COBI/FTC/TDF) and ritonavir-boosted atazanavir/emtricitabine/tenofovir DF (ATV+RTV+FTC/TDF) in HIV–1–infected, treatment-naïve subjects through 144 weeks.Method : This was a randomized, double-blind, phase 3 study. HIV-1 protease (PR) and reverse transcriptase (RT) were sequenced at screening. Genotypic and phenotypic analyses were performed at virologic failure confirmation and retrospectively at baseline for PR, RT, and integrase (IN) for patients with virologic failure through week 144.Results: In the EVG/ COBI/FTC/TDF group through week 144, HIV-1 from 8 patients (2.3%; 8/353 treated patients) developed primary IN strand transfer inhibitor (INSTI) (n = 6) and/or nucleoside RT inhibitor (NRTI) resistance substitutions (n = 7). The emergence of resistance decreased after the first year, with 5 patients developing HIV-1 resistance through week 48, 1 from weeks 48-96, and 2 from weeks 96-144. Emergent substitutions were E92Q, N155H, or Q148R (n = 2 each) and T66I or T97A (n = 1 each) in IN and M184V/I (n = 7) and K65R (n = 1) in RT. All 8 isolates had reduced susceptibility to EVG, FTC, or TDF. Virus with EVG phenotypic resistance showed cross-resistance to raltegravir. In the ATV+RTV+FTC/TDF group, HIV-1 from 2 patients (0.6%; 2/355 treated patients; both at week 144) developed the resistance substitution M184V/I in RT.Conclusions: Resistance development to EVG/COBI/FTC/TDF was infrequent (2.3%) through 144 weeks of therapy and decreased over time, consistent with durable efficacy.